A CORM loaded nanoplatform for single NIR light-activated bioimaging, gas therapy, and photothermal therapy in vitro. Issue 44 (26th October 2021) - Pei, Shihao; Li, Jia-Bei; Wang, Zhuo; Xie, Yao; Chen, Jiabo; Wang, Haifang; Sun, Lining
Abstract : A single light irradiated multifunctional nanoplatform was developed for upconversion luminescence imaging guided photothermal therapy and gas therapy. This versatile nanoplatform can be a promising candidate for the effective treatment of cancer cells. Abstract : Carbon monoxide (CO) can cause mitochondrial dysfunction, inducing apoptosis of cancer cells, which sheds light on a potential alternative for cancer treatment. However, the existing CO-based compounds are inherently limited by their chemical nature, such as high biological toxicity and uncontrolled CO release. Therefore, a nanoplatform – UmPF – that addresses such pain points is urgently in demand. In this study, we have proposed a nanoplatform irradiated by near-infrared (NIR) light to release CO. Iron pentacarbonyl (Fe(CO)5 ) was loaded in the mesoporous polydopamine layer that was coated on rare-earth upconverting nanoparticles (UCNPs). The absorption wavelength of Fe(CO)5 overlaps with the emission bands of the UCNPs in the UV–visible light range, and therefore the emissions from the UCNPs can be used to incite Fe(CO)5 to control the release of CO. Besides, the catechol groups, which are abundant in the polydopamine structure, serve as an ideal locating spot to chelate with Fe(CO)5 ; in the meantime, the mesoporous structure of the polydopamine layer improves the loading efficiency of Fe(CO)5 and reduces its biological toxicity. The photothermal effect (PTT) of the polydopamine layer is highly controllable by adjusting the external laser intensity, irradiation time and the thickness of the polydopamine layer. The results illustrate that the combination of CO gas therapy (GT) and polydopamine PTT brought by the final nanoplatform can be synergistic in killing cancer cells in vitro . More importantly, the possible toxic side effects can be effectively prevented from affecting the organism, since CO will not be released in this system without near-infrared light radiation.